Teores e estoques de nitrogênio do solo sob diferentes usos e manejos nos biomas caatinga e cerrado - Soares, Liliane da Silva (2018)
Modifications in the systems of use and management of the soil for the accomplishment of anthropic actions, provoke the alterations in the physical, physical and biological characteristics of the soil, mainly in the substitution of the organic matter of the ground (MOS) modifying, thus, the contents and the nitrogen stocks (N) of Brazilian biomes. In this context, the objective of this study was to evaluate the levels of N in its nitric and ammonia forms in soils under different uses and management in the Caatinga and Cerrado biomes. The present research was carried out in the Cerrado of Piauí in the Quilombo mountain range, located in the municipality of Bom Jesus, and the site of Caatinga was developed in the municipality of Santa Luz, located in Piauí. The treatments consisted of two biomes (Caatinga and Cerrado), three land uses (native vegetation, pasture and agriculture) and seven soil depths in the profile (0 - 10, 10 - 20, 20 - 30, 30 - 40, 40 60-60-80 and 80-100 cm). The variables analyzed were: total N and mineral N (nitrate and ammonium) and by difference, the organic N and the N stock were estimated. According to the results, the conversion of soil use from ecosystems to agroecosystems promotes increases in organic N and N stock in the Caatinga biome. The conversion of native vegetation to pasture or agriculture in the Cerrado biome promotes increases in the values of all variables studied in the 0-20 cm arable layer, mainly in pasture. Regardless of the evaluated biome, it was observed that the values of the different forms of nitrogen in the soil decreased with increasing depth in all management systems (native vegetation, pasture and agriculture). The conversion of a natural system to agricultural use is something that may or may not cause impacts on soil nitrogen contents, as it was presented in this study, the substitution of native vegetation in the Caatinga and Cerrado biomes for agricultural use (agriculture and pasture) conditioned higher levels of nitrogen to the soil when compared to those found in native vegetation.